The role of the Internet Meme in a controversy about racial and cultural representation regarding the first two Netflix productions in Peru - Gozalo Bohl, Rodrigo (CIC. Cuadernos de Información y Comunicación, 2023)
The following study analyses Internet meme’s function in a public digital controversy about racial and cultural representation in Peru. Memes, signs and texts that configure discourses, allow us to access new and different public’s perspectives. Because of how they circulate in the public digital sphere they can achieve a significative impact on the topics that receive people’s attention as part of the debate. Nonetheless, as they expand discourse reach, they also negatively affect critical and reflective thinking, as well as dialogue between individuals and groups.